Frequent Questions about our Solver

The problem

Click to see the original problem


Need help understanding why this equation is incorrect

Answer provided by our tutors

In order to solve this inequality we need to graph:

y = (×+3)(×-4) - 7

and see for what values of 'x' the graph for 'y' goes below the x-axis:

Click here to see the graph


We will find the zeros by solving:

(×+3)(×-4) - 7 = 0


Click here to see the step by step solution for 'x'


x1 = 4.89 approximately

x2 = -3.89 approximately

So, the solution for the inequality '(×+3)(×-4)<7' is the interval (-3.89, 4.89). 

← Previous Problem Next Problem →